INSTRUMENTS OF ENVIRONMENTAL AUDIT IN SEKTORAL ENVIRONMENTAL MANAGEMENT SYSTEM - Lebedevych , Svitlana (Forestry, Forest, Paper and Woodworking Industry, 2011)
The importance of introduction of environmental audit into sectoral system of ekomanagement is emphasized. The set of developed instruments for introducing environmental audit was characterized and described by the example of forest sector of Ukraine.